White-nose syndrome fungus: a generalist pathogen of hibernating bats - Zukal, Jan; Bandouchova, Hana; Bartonicka, Tomas; Berkova, Hana; Brack, Virgil; Brichta, Jiri; Dolinay, Matej; Jaron, Kamil S; Kovacova, Veronika; Kovarik, Miroslav; Martínková, Natália; Ondracek, Karel; et al. (PloS one, 2014)
Host traits and phylogeny can determine infection risk by driving pathogen transmission and its ability to infect new hosts. Predicting such risks is critical when designing disease mitigation strategies, and especially as regards wildlife, where intensive management is often advocated or prevented by economic and/or practical reasons. We investigated Pseudogymnoascus [Geomyces] destructans infection, the cause of white-nose syndrome (WNS), in relation to chiropteran ecology, behaviour and phylogenetics. While this fungus has caused devastating declines in North American bat populations, there have been no apparent population changes attributable to the disease in Europe. We screened 276 bats of 15 species from hibernacula in the Czech Republic over 2012 and 2013, and provided histopathological evidence for 11 European species positive for WNS. With the exception of Myotis myotis, the other ten species are all new reports for WNS in Europe. Of these, M. emarginatus, Eptesicus nilssonii, Rhinolophus hipposideros, Barbastella barbastellus and Plecotus auritus are new to the list of P. destructans-infected bat species. While the infected species are all statistically phylogenetically related, WNS affects bats from two suborders. These are ecologically diverse and adopt a wide range of hibernating strategies. Occurrence of WNS in distantly related bat species with diverse ecology suggests that the pathogen may be a generalist and that all bats hibernating within the distribution range of P. destructans may be at risk of infection.
Keywords: Chiroptera; Biodiversity; Risk; Ascomycota; riziko; zvířata; Phylogeny; fylogeneze; biodiverzita; Hibernation; hibernace; Animals